Chest X-ray interpretation. (2nd May 2019) - Dawkes, Susan; O'Reilly, Michelle
Abstract : The chest X-ray is a common, low-cost investigation that is an important aid in cardiovascular disease diagnosis. Although newer, more sophisticated modalities of imaging are available, chest X-rays remain fundamental, first-line investigations used to determine patient care. Although a radiologist should report all X-rays, nurses and other health professionals frequently examine and interpret chest X-rays. A sound knowledge of normal anatomy and physiology is fundamental. The technical quality of the chest X-ray, specifically the projection of the film, its orientation, rotation of the patient and penetration of the X-rays is important to determine. To prevent abnormalities going undetected when examining chest X-rays, a comprehensive systematic approach to assessment and interpretation is essential. Common abnormalities seen on X-rays from patients with cardiovascular disease have specific differentiating features and these, combined with the physical examination of the patient, will allow for faster diagnosis and early medical intervention.